THE MORAL MESSAGE IN THE LITTLE MOM FILM - Siti Ailani Yonaski; Hery Supiarza (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Film is a tool to convey various messages to audiences through a story medium. There are so many moral messages contained in a film. In Indonesia itself has produced many films which are not solely for entertainment, but also provide a moral message for the audience. Moral itself means Etymologically, the word moral comes from the Latin word mos, the plural form is mores, which means ordinances or customs. In the Big Indonesian Dictionary (1989: 592), moral is defined as morals, character, or morality. Departing from this phenomenon, the author decided to conduct this study more deeply by examining the moral messages contained in the film Little Mom, in understanding the author's moral message using Charles Sanders Pierce's semiotic analysis. The purpose of this study was to determine the moral message in the film Little Mom based on Charles Sanders Peirce's analysis. The type of research used is qualitative with descriptive method, the results of this study indicate that the film Little Mom with 13 episodes, there are moral messages about responsibility, consequences, sex education, teaching to do things that have not been legalized and think before doing anything. And this film can also be an example for those who are in the same problem or problem raised in this film, namely pregnancy out of wedlock.